(untitled) (The International Journal for Scientific Research, 2025)
This study focuses on the possibility of reviving consensus (al-ʾiǧmāʿ), considered to be one of the recognized sources of Islamic legislation, in the light of the development of contemporary technological means. The importance of the subject lies in the fact that it addresses one of the most debated issues in the foundations of jurisprudence (ʾuṣūl al-fiqh), especially since many ancient scholars denied the practical feasibility of consensus (al-ʾiǧmāʿ) citing the geographical dispersion of the ulama, the difficulty of verifying their consensus and the impossibility of transmitting it to the community. The study responds to the following problem: how can current technological means overcome the obstacles that have led some scholars to question the possibility of consensus (al-ʾiǧmāʿ), thus making it possible to achieve, prove and disseminate it within the Muslim community today? The aim of the research is to study consensus (al-ʾiǧmāʿ) and the position of ancient scholars towards it, while examining the technological tools that can facilitate it today. The approach adopted is based on the documentary method (analysis of books and online sources) and content analysis. The main results show that it is now easier and more accurate to identify the ulama eligible to legislate (al-ijtihād) thanks to digital databases and platforms, and that the modern technological boom has removed the barriers to achieving and disseminating consensus (al-ʾiǧmāʿ), via virtual means of communication and digital dissemination. In conclusion, the research recommends promoting consensus (al-ʾiǧmāʿ) today, in decision-making, by exploiting contemporary technological tools, through the creation of specialized digital platforms, databases for ulama and the organization of virtual conferences bringing together scholars from the Islamic world, thus offering greater flexibility to Islamic legislation in the face of modern challenges.